The level of lipopolysaccharide-binding protein is significantly increased in plasma in patients with the systemic inflammatory response syndrome. - Myc, A (1997)
Currently, there is no way to predict with a high degree of sensitivity and specificity which patients are likely to develop systemic inflammatory response syndrome (SIRS) following systemic infection, trauma, organ rejection, or blood loss. The level of human lipopolysaccharide-binding protein (LBP) was determined in the plasma of 22 patients with a clinical diagnosis of early SIRS. Twenty-nine plasma samples from healthy volunteers were used as controls. The mean level of LBP in the plasma of healthy volunteers was 7.7 micrograms/ml (standard deviation, 6.2 micrograms/ml). Twenty-one of 22 patients (95%) with SIRS had an LBP level on admission at least 2 standard deviations above the mean LBP level for a healthy volunteer control group (range, 4.9 to 114.2 micrograms/ml; mean, 36.6 micrograms/ml; standard deviation, 22.2 micrograms/ml; P < 0.0001). The level of LBP in the plasma of the majority of patients with early SIRS is significantly increased compared to that in healthy controls. The sensitivity, specificity, and predictive value of elevated plasma LBP levels in patients with SIRS remain to be determined.